WAKAF SEBAGAI INSTRUMEN KEMANDIRIAN EKONOMI SEKOLAH: STUDI PADA SMK IB KHALIFAH BANGSA METRO (PINK CAMPUS) - Istikomah, Annisa; Aristianti, Desta Ayu; Wati, Cahyani Dwi Era; Muda, Rini Agustin; Aulia, Amanda; Zulaikha, Siti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Waqf is one of the important instruments in Islamic economics that has great potential in supporting development, especially in the field of education. This study aims to analyze the role and benefits of waqf in developing economic independence at SMK IB Khalifah Bangsa Metro (Pink Campus). This study uses a descriptive qualitative methodology. Data were collected through comprehensive interview methods, observation, and documentation. Informants in this study include the school, principal, teachers, and the community. The data used consists of primary and secondary sources. Primary data includes interviews and observations. Meanwhile, secondary data includes scientific texts, including journals and other publications. The results of the study indicate that productive waqf management at SMK IB Khalifah Bangsa is able to support the operational needs of the school, finance educational programs, and encourage student entrepreneurial activities. In addition, this waqf management also has a positive impact on the economic empowerment of the surrounding community. These findings indicate that waqf can be a strategic resource in creating economic independence for educational institutions based on Islamic values. This study recommends strengthening productive waqf management as part of the sustainability strategy of educational institutions. ABSTRAK Wakaf merupakan salah satu instrumen penting dalam ekonomi Islam yang memiliki potensi besar dalam mendukung pembangunan, khususnya di bidang pendidikan. Penelitian ini bertujuan untuk menganalisis peran dan manfaat wakaf dalam pengembangan kemandirian ekonomi di SMK IB Khalifah Bangsa Metro (Kampus Pink). Penelitian ini menggunakan metodologi kualitatif deskriptif. Data dikumpulkan melalui metode wawancara komprehensif, observasi, dan dokumentasi. Informan dalam penelitian ini meliputi pihak sekolah, kepala sekolah, guru, dan masyarakat. Data yang digunakan terdiri dari sumber primer dan sekunder. Data primer meliputi wawancara dan observasi. Sementara itu, data sekunder meliputi teks ilmiah, termasuk jurnal dan publikasi lainnya. Hasil penelitian menunjukkan bahwa pengelolaan wakaf secara produktif di SMK IB Khalifah Bangsa mampu menopang kebutuhan operasional sekolah, membiayai program pendidikan, serta mendorong aktivitas kewirausahaan siswa. Selain itu, pengelolaan wakaf ini juga berdampak positif pada pemberdayaan ekonomi masyarakat sekitar. Temuan ini menunjukkan bahwa wakaf dapat menjadi sumber daya strategis dalam menciptakan kemandirian ekonomi lembaga pendidikan berbasis nilai-nilai Islam. Penelitian ini merekomendasikan penguatan manajemen wakaf produktif sebagai bagian dari strategi keberlanjutan lembaga pendidikan.